2012
DOI: 10.1111/j.1574-6941.2011.01264.x
|View full text |Cite
|
Sign up to set email alerts
|

Facultative diazotrophy increases Cylindrospermopsis raciborskii competitiveness under fluctuating nitrogen availability

Abstract: Relative fitness of three bloom-forming and potentially toxic cyanobacteria from the subtropical St. John's River, Florida was investigated under a range of nutrient conditions, during a bloom dominated by Cylindrospermopsis raciborskii. Nitrogen (N) was the primary nutrient limiting phytoplankton primary productivity and biomass. Phytoplankton biomass was also enhanced by phosphorus (P) added either alone or jointly with N, suggesting different components of the phytoplankton experienced distinct nutrient lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 48 publications
4
54
1
3
Order By: Relevance
“…Recent phylogenetic evidence has suggested that the species originated in the American tropics (Moreira et al, 2015) and its distribution was once thought to be restricted to the tropics and subtropics, where it co-occurs with other bloom-formers such as Microcystis aeruginosa and Anabaena sp. (Marinho & Huszar, 2002;Molica et al, 2005;Soares et al, 2009;Moisander et al, 2012). However, it has increasingly been found in temperate regions, most recently in Europe and North America (Hong et al, 2006;Conroy et al, 2007;Kling, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…Recent phylogenetic evidence has suggested that the species originated in the American tropics (Moreira et al, 2015) and its distribution was once thought to be restricted to the tropics and subtropics, where it co-occurs with other bloom-formers such as Microcystis aeruginosa and Anabaena sp. (Marinho & Huszar, 2002;Molica et al, 2005;Soares et al, 2009;Moisander et al, 2012). However, it has increasingly been found in temperate regions, most recently in Europe and North America (Hong et al, 2006;Conroy et al, 2007;Kling, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…Our analyses showed that C. raciborskii was now a dominant species in samples from ES, HU and NL. This species has rapidly increased all over the world from tropical to temperate zones (Fabbro & Duivenvoorden., 1996;Chapman & Schelske., 1997;Lagos et al, 1999;Shafik et al, 2001;Briand et al, 2004;Valerio et al, 2005;Bouvy et al, 2006;Fastner et al, 2007;Moustaka-Gouni et al, 2009;Alster et al, 2010;Kokociński et al, 2010;Moisander et al, 2012) limneticus, are particularly known from meso-and eutrophic water bodies and may form water blooms Nixdorf et al, 2003;Reynolds et al, 2002;Cronberg & Annadotter, 2006;Willén, 2007). Phillips et al (2012) classified phytoplankton genera into very tolerant, tolerant, sensitive and very sensitive taxa of high nutrient conditions.…”
Section: Gonyostomum Semen Is a Well-known Nuisance Alga With Widesprmentioning
confidence: 99%
“…Posselt et al (2009) showed that dominance of this cyanobacterium can be favoured in lakes with fluctuating P supply, and amaral et al (2014) recently demonstrated growth optimization of phosphate-deficient C. raciborskii to short-term nutrient fluctuations in P supply, which was attributed to its physiological flexibility. Cylindrospermopsis raciborskii tolerance to low light levels (Briand et al, 2004), the capacity to fix atmospheric n 2 (Moisander et al, 2012), phenotypic plasticity concerning pigments, size and growth rates (Bonilla et al, 2012), together with the competitive advantages concerning P mentioned above, probably have contributed to the success of this species, maintaining high Chl-a concentration in the low nutrient context (specially P) of Peri Lake. according to amaral et al (2014), the adaptive behavior of this species may help to explain its invasive success in a wide range of aquatic ecosystems where P is frequently the limiting resource.…”
Section: Nutrient Limitation and Chlorophyll A Relationshipsmentioning
confidence: 99%